Shopping Lifestyle As A Moderating Variable Of The Influence Of Hedonic Shopping Value On Impulse Buying - Sulistyo Budi Utomo; Rudy Irwansyah; Asriany; Dikky Mooy; Risca Kurnia Sari (LP2M IAIN Palopo, 2025)
This study aims to analyze and test the role of Shoppng Lifestyle variables as moderating variables in strengthening or weakening the influence of Hedonic Shopping Value (HSV) on Impulsive Buying (IB). Impulsive buying is a consumer behavior phenomenon characterized by lack of planning, quick decisions, and strong emotional drives, which often have significant financial consequences, especially in the context of e-commerce and stimulation-rich retail environments. Previous research has confirmed that hedonic value, namely the aspects of pleasure, excitement, and fantasy obtained from the shopping process, is a strong predictor of impulsive tendencies . However, the magnitude of this influence is believed not to be universal, but rather depends on the individual context, one of which is the internalized consumption pattern, namely shopping lifestyle. This study adopts the StimulusOrganismResponse (S-O-R) framework, where HSV serves as an internal stimulus (O) that triggers an impulsive buying response (R), and this interaction is moderated by shopping lifestyle. This study employed a quantitative design with a survey of active online shoppers in Indonesia. The target population was individuals with moderate to high levels of hedonic consumption. The analytical technique used was Moderated Regression Analysis (MRA) to test the moderation hypothesis. It is hoped that the findings of this study will provide theoretical contributions by validating shopppng lifestyle as an important contextual variable in consumer behavior models and provide practical implications for retailers in designing marketing strategies that target consumers based on their lifestyle profiles.